THE ROLE OF ELECTRIC SHOCK IN IMPROVEMENT OF SOME OKRA TRAITS AND TESTED UNDER PROTECTED CULTIVATION CONDITIONS - & Alwan, Al-Karagholi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This experiment Carried out at the Dept. of Research and Studies– office of Horticulture- Ministry of Agriculture at Abu Ghraib, for two seasons in 2014 and 2015. The objective of the experiment  to stady the effect of electric shocks on some okra (Abelmoschus esculentus L. Moench) traits  study. Six pure lines (S1 , S2, , S3 , S4 , S5 , S6) were attached  with four levels of electric shock (0, 9, 12 and 15 amp for 5 minutes) The 24 treatments were planted according to the RCBD with tow replicates to produce plants of the first generation  on which the selection is to get the seeds of the second generation. A factorial experiment within RCBD with three replicates, were used  in the plastic house. The results revealed that the electric current for the second season improved most of the traits vegetative and flowering  growth okra plants, The treatment S3A15 was superion  in traits, leaves number and flowers number  and pods  number and yield per plant, which were(117.10 leave and 122.60 Flower and 98.17 Pod and 519.87 g), while S4A15 treatment gave the highest plant height, days number of the appearance for first flower and days number for the first fruit setting, which were (175.13 cm and 87.66 days and 89 days). S1A15 treatment has given the highest value of fruit set percentage, which were 84.60, while S6A15 gave the highest pod weight 6.50 g, also S5A15 produced highest value of seeds number in pods (70 seed). S1A12 gave the highest leaves number before the first flower was 2.90 leave, Results revealed that the seed treatment with electric shock improved  some field traits in okra.